Intravenous pamidronate in the treatment of severe idiopathic infantile hypercalcemia - Skalova, Sylva; Cerna, Lucie; Bayer, Milan; Kutilek, Stepan; Konrad, Martin; Schlingmann, Karl-Peter (Iranian journal of kidney diseases.., 2013)
Idiopathic infantile hypercalcemia (IIH) is a rare disorder caused by CYP24A1 loss-of-function mutation, resulting in impaired degradation of 1,25-dihydroxyvitamin D3. Pamidronate, an intravenously administered bisphosphonate, which is a potent inhibitor of bone resorption, has been reported only once for treatment IIH. We present a case of a previously healthy 5-month-old boy with IIH, where calcemia peaked to 5 mmol/L. Treatment with methylprednisone and furosemide had only minor effects; therefore, 2 intravenous infusions of pamidronate (0.6 mg/kg per dose) corrected the serum calcium level to 2.95 mmol/L. Furthermore, CYP24A1 homozygous mutation p.R396W (c.1186c>t) was identified in this patient, confirming the clinical diagnosis of IIH. In conclusion, IIH has a favorable outcome once properly detected and appropriately treated. Pamidronate has a beneficial effect in those patients with IIH where glucocorticoids and furosemide fail to meet the expectations.
Keywords: inhibitory kostní resorpce; Calcium; Bone Density Conservation Agents; Pamidronate; Infant; Humans; diferenciální diagnóza; Vitamin D3 24-Hydroxylase; kojenec; vápník; mutace; Hypercalcemia; výsledek terapie; Diagnosis, Differential; lidé; Biomarkers; pamidronát; steroidhydroxylasy; předškolní dítě; Steroid Hydroxylases; biologické markery; Male; CYP24A1; Treatment Outcome; Mutation; mužské pohlaví; bisfosfonáty; Child, Preschool; hyperkalcemie; Diphosphonates